2018
DOI: 10.1021/acsomega.8b01099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a PEGylated Dopamine Ester with Enhanced Antibacterial and Antifungal Activity

Abstract: Drug–polymer conjugation is a simple and efficient approach to synthesizing new, effective, and potent antimicrobial agents to counter the problem of microbial resistance. In the present study, a PEGylated dopamine ester (PDE) was synthesized using the PEGylation process and synthesis of PDE was confirmed by Fourier-transform infrared spectroscopy, elemental analysis (CHNS–O), and atomic force microscopy techniques. Later, the antimicrobial activity of PDE was assessed against four strains of bacteria (Bacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…This is due to the coordination and hydrogen‐donor of the hydroxyl groups and occupied orbitals in metal ions. [ 1 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the coordination and hydrogen‐donor of the hydroxyl groups and occupied orbitals in metal ions. [ 1 ]…”
Section: Resultsmentioning
confidence: 99%
“…DA had also been used to synthesize numerous herbicides and drugs. [ 1 ] DA is one of a good number of natural tryptamine derivatives occurring in plants and animals such as serotonin, melatonin, gramine, histamine, octopamine, norepinephrine, and epinephrine. [ 2,3 ] Tryptamine derivatives have significant properties such as neurotransmission, neuromodulation, vasoconstriction, and vasodilation and are antimicrobial, antibacterial, antioxidant, antifungal, anti‐inflammatory, and antidepressant.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the distinct signals were assigned to the structural features specific to dopamine and biochanin A (template and sample molecule). These are based on previous studies (Sekine et al, 2011;Capeletti and Zimnoch, 2016;Thakur et al, 2018) and are marked in Supplemental Figure S2B. Finally, the binding abilities were supported by MAL-DI-TOF MS imaging analysis.…”
Section: Approach Taken In This Workmentioning
confidence: 65%
“…It is also clear that the peak at 3031 cm −1 originating from C–H stretching vibrations was shifted to 3008 cm −1 and increased in intensity due to the –NH group. The peak located at 2882 cm −1 was shifted slightly to 2904 cm −1 due to alkyl C−H stretching [ 68 ]. The intensity of the observed peak around 1507 cm −1 was increased due to aromatic C=C stretching, and the peak located around 1287 cm −1 originated due to amine C–N stretching [ 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peak located at 2882 cm −1 was shifted slightly to 2904 cm −1 due to alkyl C−H stretching [ 68 ]. The intensity of the observed peak around 1507 cm −1 was increased due to aromatic C=C stretching, and the peak located around 1287 cm −1 originated due to amine C–N stretching [ 68 , 69 ]. These findings confirmed the reaction between DA and CQD film and revealed that once DA was introduced, the functional groups of CQDs altered conformationally.…”
Section: Resultsmentioning
confidence: 99%